Food, fat and family: Thinking fathers through mothers' words - Tanner, C.; Peterson, A.; Fraser, Suzanne (Elsevier Ltd, 2014)
In targeting parenting and the family with advice on healthy eating and exercise, contemporary childhood obesity discourse draws attention to mothers as primary carers. In the process, fathers' roles and responsibilities in promoting healthy lifestyles and in family food work are neglected or silenced. This article addresses the silence surrounding fathers' participation in the feeding of their families. To do so we draw on qualitative data from an Australian Research Council-funded study investigating the impact of childhood obesity-related health messages on families. Using Carol Gilligan's (1982) notion of the ethics of care and Ann Phoenix's (2010) concept of ‘intertextuality’ and silence in the qualitative research process, we offer an ‘intertextual’ reading of mothers' presentations of fathers' involvement in family food provisioning. Mothers' accounts reveal how gender is relationally produced in the context of parental food work, with descriptions of maternal expertise, altruism and commitment to health being contrasted with stories of paternal authority, complacency and selfishness.